2020
DOI: 10.3390/bs10080127
|View full text |Cite
|
Sign up to set email alerts
|

Customer Value Types Predicting Consumer Behavior at Dutch Grocery Retailers

Abstract: The purpose of this paper is to profile three grocery retail formats (non-discounter, soft discounter, and hard discounter) in the Netherlands using Holbrook’s value types. These value types are linked to three consumer behavior outcomes, i.e., Satisfaction, Repurchase intention, and Word-of-Mouth. The impact of the retail formats is evaluated on the importance and performance of the value types, using a questionnaire for each of the retail formats. The relationship between the value types and outcomes is test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Therefore, the non-probability sampling (convenience sample) approach employed in this research may have presented some limitations. Also, the limited sample size used in this research constitutes a source of limitation in relation to generalizability of research findings (Janssens et al, 2020). In addition, the combinations of respondents/executives from different industrial sectors in this research may have posed certain limitations.…”
Section: Discussion Of Findings Conclusion and Recommendationsmentioning
confidence: 96%
“…Therefore, the non-probability sampling (convenience sample) approach employed in this research may have presented some limitations. Also, the limited sample size used in this research constitutes a source of limitation in relation to generalizability of research findings (Janssens et al, 2020). In addition, the combinations of respondents/executives from different industrial sectors in this research may have posed certain limitations.…”
Section: Discussion Of Findings Conclusion and Recommendationsmentioning
confidence: 96%
“…Loyalty is measured in terms of a tourist’s intention to revisit or recommend the destination to others [ 50 ]. Tourist perception is an important antecedent of destination loyalty [ 51 , 52 ] and has a significant positive effect on tourists’ intention to revisit [ 53 ]. Liu et al found that emotional, functional, and social values in perceived value indirectly influence tourist loyalty through the mediating effect of well-being [ 39 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…CPV as a source of the core competitiveness provides a foundation for understanding consumer behavior and decision process in retailing [29]. Woodruff proposed that the product attributes, attribute performance, and results generated by the use of products that achieve or hinder customer goals determine consumers' perceived preference and evaluation, namely customer perceived value [30].…”
Section: Consumer Perceived Value (Cpv)mentioning
confidence: 99%